(1Z,2Z)-1,2-Bis{2-[3,5-bis(trifluoromethyl)phenyl]hydrazinylidene}-1,2-bis(4-methoxyphenyl)ethane including an unknown solvate - Mehmet Akkurt; Namiq Q. Shikhaliyev; Ulviyya F. Askerova; Sevinc H. Mukhtarova; Gunay Z. Mammadova; Flavien A. A. Toze (IUCrData, 2019)
The complete molecule of the title compound, C32H22F12N4O2, is generated by a crystallographic twofold axis aligned parallel to [010]. The F atoms of one of the CF3 groups are disordered over three orientations in a 0.6: 0.2: 0.2 ratio. In the crystal, molecules are linked by N—H...O hydrogen bonds, forming zigzag chains propagating along the a-axis direction. In addition, weak C—H...O and C—H...F bonds are observed. The contribution of the disordered solvent to the scattering was removed using the SQUEEZE routine [Spek (2015). Acta Cryst. C71, 9–18] of PLATON. The solvent contribution is not included in the reported molecular weight and density.